The Development of Moisture Sensitivity Test for Compacted Asphalt - Shamshuddin, M.K.; Abdullah, M.E.; Rhasbudin Shah3, S.M. (International Journal of Integrated Engineering, 2011)
Moisture damage is one of the major issues in asphalt distress. It is due to the adhesive and cohesive failure of asphalt mixture and it will shorten pavement life. Moisture-sensitive mixtures need to be identified during the course of the mixture design process which fulfills the specified minimum standard. The laboratory testing procedures currently available for compacted Hot Mix Asphalt (HMA) to test the moisture sensitivity were primarily developed to determine the degree of resistance to moisture damage by a particular combination of asphalt and aggregate. These moisture sensitivity tests evaluate the effect of moisture damage in laboratory by measuring the relative change of a single parameter before and after conditioning (i.e., Tensile Strength Ratio, Resilient Modulus Ratio). The tests were simple to conduct and widely accepted by various state and federal agencies, but their drawback include the empirical nature of the procedures, the dependence of the results on the moisture conditioning methodology and in several cases, the poor correlation with field performance. Many new approaches were conducted to overcome the weaknesses of the existing method. These new approaches mostly designed to conduct the test as close as the field condition and consider the material properties of asphalt to give the useful result for the asphalt performance. For better asphalt mixture design, it needs to have the test procedure which considered the effect of traffic loading. The moisture conditioning methodology should avoid using the vacuum saturation method since this method contributes to the asphalt mixture strength. The scale of performance measurement can be conducted either microscale or macroscle. Besides that the test also must be repeatable, reproducible, feasible, practical, and economical enough that it can be included in routine asphalt mixture design practice.